2018
DOI: 10.3762/bjnano.9.53
|View full text |Cite
|
Sign up to set email alerts
|

Electron interactions with the heteronuclear carbonyl precursor H2FeRu3(CO)13 and comparison with HFeCo3(CO)12: from fundamental gas phase and surface science studies to focused electron beam induced deposition

Abstract: In the current contribution we present a comprehensive study on the heteronuclear carbonyl complex H2FeRu3(CO)13 covering its low energy electron induced fragmentation in the gas phase through dissociative electron attachment (DEA) and dissociative ionization (DI), its decomposition when adsorbed on a surface under controlled ultrahigh vacuum (UHV) conditions and exposed to irradiation with 500 eV electrons, and its performance in focused electron beam induced deposition (FEBID) at room temperature under HV co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 101 publications
3
8
0
Order By: Relevance
“…Previous UHV surface science studies of the low energy electron-induced decomposition of adsorbed FEBID precursors have revealed that the first step in FEBID involves low energy electron-induced dissociation of the precursor, which is invariably accompanied by the desorption of one or more ligands from the precursor. After this initial electron-induced ligand loss step, continued electron exposure typically causes ligand decomposition, rather than dissociation and desorption from the surface. , Thus, any ligands remaining on the surface after the initial ligand loss step are incorporated into the deposit. Reactions that accompany FIBID, however, are far less well-understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous UHV surface science studies of the low energy electron-induced decomposition of adsorbed FEBID precursors have revealed that the first step in FEBID involves low energy electron-induced dissociation of the precursor, which is invariably accompanied by the desorption of one or more ligands from the precursor. After this initial electron-induced ligand loss step, continued electron exposure typically causes ligand decomposition, rather than dissociation and desorption from the surface. , Thus, any ligands remaining on the surface after the initial ligand loss step are incorporated into the deposit. Reactions that accompany FIBID, however, are far less well-understood.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we extend this postgrowth protocol, based on annealing under high vacuum, to deposits obtained from a heteronuclear carbonyl HFeCo 3 (CO) 12 precursor, , to produce a metallic alloy with improved both electrical and magnetic properties. Our aim was to obtain granular material embedded in a carbon matrix and investigate its magnetotransport properties outperforming the ones with higher metal content.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 compares the relative contributions of individual ionic species observed in DEA and DI of Mo(CO) 6 . Similar to the approach in [55][56][57], the relative DEA contributions were obtained by integrating the negative ion yield over the whole width of individual contributions in the ion yield curves for each anionic fragment. These were then normalized to the [Mo(CO) 5 ] − contribution, which is set to 1.…”
Section: Dissociative Ionization Dissociative Electron Attachment And...mentioning
confidence: 99%